One-Pot Access to 4-Aryl-2-arylacetoxynaphthalenes via Benzannulation of Oxygenated Arylacetic Acids and Alkyl Aryl Ketones - Chang, Meng-Yang; Chen, Shin-Mei; Hsiao, Yu-Ting (Synthesis, 2020)
Trifluoroacetic anhydride mediated one-pot intermolecular formal (4+2) benzannulation of oxygenated arylacetic acids with alkyl aryl ketones provides 4-aryl-2-arylacetoxynaphthalenes in moderate to good yields in the presence of H3PO4 in an open-vessel in a straightforward procedure. A plausible mechanism is proposed and discussed. This protocol provides a highly effective ring-closure via two carbon–carbon (C–C) and one carbon–oxygen (C–O) bond-formation events.
Keywords: trifluoroacetic anhydride; benzannulation; arylacetic acids; 4-aryl-2-arylacetoxynaphthalenes; easy operation